The Role of Eukaryotic and Prokaryotic ABC Transporter Family in Failure of Chemotherapy - El-Awady, Raafat; Saleh, Ekram; Hashim, Amna; Soliman, Nehal; Dallah, Alaa; Elrasheed, Azza; Elakraa, Ghada (Frontiers in Pharmacology, 2017)
Over the years chemotherapy failure has been a vital research topic as researchers have been striving to discover reasons behind it. The extensive studies carried out on chemotherapeutic agents confirm that resistance to chemotherapy is a major reason for treatment failure. “Resistance to chemotherapy” however, is a comprehensive phrase that refers to a variety of different mechanisms in which ATP-binding cassette (ABC) mediated efflux dominates. The ABC is one of the largest gene superfamily of transporters among both eukaryotes and prokaryotes; it represents a variety of genes that code for proteins, which perform countless functions, including drug efflux - a natural process that protects cells from foreign chemicals. Up to date, chemotherapy failure due to ABC drug efflux is an active research topic that continuously provides further evidence on multiple drug resistance (MDR), aiding scientists in tackling and overcoming this issue. This review focuses on drug resistance by ABC efflux transporters in human, viral, parasitic , fungal and bacterial cells and highlights the importance of the MDR permeability glycoprotein (P-gp) being the mutual ABC transporter among all studied organisms. Current developments and future directions to overcome this problem are also discussed